PENGARUH MUROTTAL SURAH AR-RAHMAN TERHADAP KECEMASAN PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA - Daniarti, Dian; Novitayanti, Eka (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2024)
ABSTRAKPerawatankecemasanpasienhemodialisadapatmencakupteknikrelaksasi dan distraksi. Alternatifuntukpengobatangangguanfisik, mental, dan psikologisadalahterapimusik spiritual ataumurotal, salah satuterapipsikoreligiussaat ini mulaiberkembang di dunia adalahterapi Al-Qur'an surah Ar-Rahman.UntukmengetahuipengaruhMurottal Surah Ar-Rahmanterhadapkecemasanpasiengagalginjalkronik di ruanghemodialisa.Jenis penelitian yang digunakandalampenelitianiniadalaheksperimentaldenganmetodequasyexperimendenganpendekatantwo group pre-post test design.Jumlahsampeldalampenelitian 48 responden (24 kelompokintervensi dan 24 kelompokkontrolpasiengagalginjal yang melakukanhemodialisa 2x seminggudengantekhnik total sampling, analisis datamenggunakan uji wilcoxondan analisis uji mann-whitney.Hasil penelitian pada kelompokkontrolpre-post test surah Ar-Rahmanmenunjukkannilai rata-rata kecemasantidakterjadiperubahan yang signifikanPvalue = 0,059 > 0,05. Kelompokeksperimenmenunjukkanadanyaperubahanyaitupenurunan rata-rata tingkatkecemasandarisedangmenjadiringan, P value = 0,002. P value > 0,05 disimpulkanadapengaruhterapiMurottal Surah Ar-Rahmanterhadapkecemasanpasiengagalginjalkronik di ruanghemodialisa.Kata Kunci :Kecemasan, Murottal Surah Ar-Rahman,Hemodialisa THE EFFECT OF MUROTTAL SURAH AR-RAHMAN ON ANXIETY OF CHRONIC KIDNEY FAILURE PATIENTS IN THE HEMODIALYSIS ROOM ABSTRACTTreatment of anxiety in hemodialysis patients can include relaxation and distraction techniques. An alternative for treating physical, mental and psychological disorders is spiritual music therapy or murotal. One of the psychoreligious therapies currently starting to develop in the world is Al-Qur'an Surah Ar-Rahman therapy. To determine the effect of Murottal Surah Ar-Rahman on the anxiety of chronic kidney failure patients in the hemodialysis room. The type of research used in this research is experimental with a quasi-experimental method with a two group pre-post test design approach. The number of samples in the study was 48 respondents (24 intervention groups and 24 control groups of kidney failure patients who underwent hemodialysis twice a week using total sampling technique, data analysis using the Wilcoxon test and Mann-Whitney test analysis. The results of the research in the pre-post test control group of surah Ar-Rahman showed that the average anxiety value did not change significantly, P value = 0.059 > 0.05. The experimental group showed a change, namely a decrease in the average level of anxiety from moderate to mild, P value = 0.002. P value > 0.05, it can be concluded that there is an effect of Murottal Surah Ar-Rahman therapy on the anxiety of chronic kidney failure patients in the hemodialysis room. Keywords: Anxiety, Murottal Surah Ar-Rahman, Hemodialysis